Introduction to the Special section “Critical theory and political economy of the Internet (Nordmedia 2011)“ - Fuchs, Christian; Bolin, Göran (tripleC – Journal for a Global Sustainable Information Society)

Grounding Critical Communication Studies - Fuchs, Christian (International communication. Four-Volume Set. Volume 2)

New Marxian Times! Reflections on the 4th ICTs and Society Conference "Critique, Democracy and Philosophy in 21st Century Information Society. Towards Critical Theories of Social Media" - Fuchs, Christian (tripleC - Journal for a Global Sustainable Information Society)

Report on Theoretical Frameworks and Previous Empirical Research. Deliverable D1.1 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Amicelle, Anthony; Bus, Jacques; El-Baba, Taghrid; Fuchs, Christian; Mordini, Emilio; Rebera, Andrew; Robinson, Neil; Trottier, Daniel; Venier, Silvia; Wright, Steve

Societal Impact Report. Deliverable D1.4 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Mordini, Emilio; Bus, Jacques; Rebera, Andrew P.; Venier, Silvia; McCarthy, Sadhbh; Hayes, Ben; Wright, Steve; Deering, Daniel; Fuchs, Christian; Trottier, Daniel; Krieglsteiner, Susann; El-Baba, Taghrid

NO2 Sensors with Reduced Power Consumption Based on Mesoporous Indium Oxide - Donato, Nicola; Wagner, Thorsten; Tiemann, Michael; Waitz, Thomas; Kohl, Claus-Dieter; Latino, Mariangela; Neri, Giovanni; Spadaro, Donatella; Malagù, Cesare (Lecture Notes in Electrical Engineering)
We report on sensing properties of ordered mesoporous nanostructures of In2O3 synthesized by nanocasting procedure towards NO2. The nanostructured material shows improved recover times and higher responses compared to non nanostructured material at low operating temperatures (100–150°C) thus allowing the use for low power NO2 sensors. These properties may be related to fast oxygen in and out propagation facilitated by an enhanced surface accessibility of the nanostructure.

Research Design & Data Analysis, Presentation, and Interpretation: Part One - Allmer, Thomas

Towards a Critical Theory of Surveillance in Informational Capitalism - Allmer, Thomas

Weltliche deutsche Lieder in Messvertonungen des 15. und 16. Jahrhunderts. Eine erste Annäherung an das Repertoire - Höink, Dominik (Polyphone Messen im 15. und 16. Jahrhundert. Funktion, Kontext, Symbol)

Freiheit Macht Spaß. Zur Gouvernementaliät des Vergnügens - Hälterlein, Jens (Die vergnügte Gesellschaft. Ernsthafte Perspektiven auf modernes Amüsement)

Die Kritik der Konsumgesellschaft und die Praxis des Konsums - Hälterlein, Jens (Transnationale Vergesellschaftung. Verhandlungen des 35. Kongresses der Deutschen Gesellschaft für Soziologie in Frankfurt am Main 2010)

A normal form for definite quadratic forms over $\mathbb{F}_{q}[t]$ - Kirschmer, Markus (Mathematics of Computation)
An efficient algorithm to compute automorphism groups and isometries of definite Fq[t]-lattices for odd q is presented. The algorithm requires several square root computations in Fq₂ but no enumeration of orbits having more than eight elements.
Keywords: Applied Mathematics; Computational Mathematics; Algebra and Number Theory

Kirchentage, Festivals, Conventions - Religiöse Happenings als Orte der Glaubensbildung - Schroeter-Wittke, Harald (Glaubensbildung. Die Weitergabe des Glaubens im europäischen Protestantismus. Formaton of Faith. Handing down Faith in European Protestantism)

Kirchentags, Festivals, Conventions - Religious Happenings as Places for the Formation of Faith - Schroeter-Wittke, Harald (Glaubensbildung. Die Weitergabe des Glaubens im europäischen Protestantismus. Formaton of Faith. Handing down Faith in European Protestantism)

Chronikbücher - ein religionspädagogischer Kommentar in der Bibel - Schroeter-Wittke, Harald (Religionspädagogischer Kommentar zur Bibel)

Auf die Plätze - Sorgen - Los. Bibelarbeit auf dem Wege zu Mt 6,19-34 (BAB_093_0140) - Schroeter-Wittke, Harald; Keuchen, Marion; Leutzsch, Martin; Weßler, Sarah-Luise (Dokumente CD-ROM des 33. DEKT Dresden 2011)

Muss die Freiheit wohl grenzenlos sein? Statement beim Feierabendmahl "Freiheit aufgetischt" am Zwinger (FRE_002_0181) - Schroeter-Wittke, Harald (Dokumente CD-ROM des 33. DEKT Dresden 2011)

Religion als Thema der Unterhaltung im populären Spielfilm - Schroeter-Wittke, Harald (Handbuch Theologie und Populärer Film Band 3)

Liebe und Sexualität - Schroeter-Wittke, Harald (Evangelischer Taschenkatechismus)

Religionspädagogischer Kommentar zur Bibel